PENGARUH PROMOSI DAN LAYANAN TERHADAP KEPUTUSAN NASABAH KREDIT USAHA MIKRO DI PT. BANK MANDIRI (PERSERO) TBK. CABANG TUGUMULYO MUSI RAWAS - Supriyanto Supriyanto; Bagus Andriansyah (Jurnal Media Ekonomi (JURMEK), 2019)
The objectives of this study are as follows: a. To determine the effect of promotion and service on the decision of micro business credit customers at PT BANK MANDIRI (PERSERO) TBK. Tugumulyo Musi Rawas Branch, b. To determine the effect of promotion on the decision of micro business credit customers at PT BANK MANDIRI (PERSERO) TBK. Tugumulyo Musi Rawas Branch, c. To determine the effect of service on the decision of micro business credit customers at PT BANK MANDIRI (PERSERO) TBK. Tugumulyo Musi Rawas Branch. Based on the results of the t test, that variable that promotion variable (X1) on the decision of micro business credit customers at PT. Bank Mandiri (Persero) Tbk. Tugumulyo Musi Rawas branch shows that the value of t = 2.788 is greater than the value of ttable 2,000 with a significant level = 0,000 <(α) 0.05, df (n-2) 57 - 2 = 55 is equal to 2,000, this shows Ho is rejected and Ha is accepted and Partially the promotion variable has a significant influence on the decision of micro business credit customers at PT. Bank Mandiri (Persero) Tbk Tugumulyo Musi Rawas Branch. Based on the results of the t test, that service variable (X2) on the decision of micro business credit customers at PT. Bank Mandiri (Persero) Tbk. The Tugumulyo Musi Rawas branch shows that the value of t count = 3.852 is greater than the value of ttable 2,000 with a significant level = 0,000 <(α) 0.05, df (n-2) 57 - 2 = 55 is equal to 2,000, this shows Ho is rejected and Ha is accepted and partially service variables have a significant influence on the decision of micro business credit customers at PT. Bank Mandiri (Persero) Tbk Tugumulyo Musi Rawas Branch. Based on the results of the F test can show that the Fcount obtained is 10.750> Ftable = 5.06 and the significance level simultaneously the significance is 0.000 <(α) = 0.05 df = n - k = 57-2-2 - 1 = 54 is 5.06 so Ho is rejected and Ha is accepted, meaning that it shows that together (simultaneously) the independent variables namely promotion and service have a significant influence on the dependent variable, namely the decision of the customer, so that the truth is proven and the hypothesis is acceptable